Plyometric performance in U13 basketball: influence of modified competitions and maturational status with GPS tracking - Aguiar, R. A. B.; García-Angulo, F. J.; Izzo, R.; Ortega-Toro, E. (Sensors, 2026)
The aim of this study was to analyze the effects of different competition formats on the plyometric performance of under-13 basketball players, considering the influence of maturational age and monitored through GPS devices. Thirty-seven under-13 male basketball players (age = 12.91 ± 0.57 years) from four southeast Spanish teams participated in two different tournaments. On the first day, the tournament was played according to the official Spanish Basketball Federation (FEB) rules for under-14 players. On the second day, the competition was held with modified rules (Modified Tournament), in which the basket height was lowered to 2.90 m and the three-point line was replaced by a rectangle located 4 m from the basket. Plyometric variables, such as number of impacts (total and in zones), number of horizontal impacts (total and in zones), number of steps, number of jumps (total and in zones) and g-force of jumps during takeoff and landing, were assessed using GPS monitoring. In addition, the moderating effect of maturational age on the intervention in each of the variables under study will be evaluated. The results showed that the modified tournament (MT) showed significant differences compared to the standard format (FEB) in playing time, steps, landings 5-8 G, and takeoffs >8 G during positional attacks, as well as in horizontal impact variables during counterattacks and effective playing time. Bayesian analysis provided moderate-to-strong evidence for several of these variables, and extreme evidence for playing time and impacts during effective time. Moreover, maturational age (%PAH) consistently moderated the intervention effects, particularly in impact loads and locomotor demands. These findings can provide useful insights for coaches and practitioners in youth basketball. Adjusting competition rules and considering maturational status may optimize player development by creating contexts that enhance plyometric performance while adapting to the physical and biological characteristics of young athletes.